Mother’s information about Weaning in Infants - البيرق كوكب (Latakia University Journal -Medical Sciences Series, 2021)
infants Weaning in is introduction of supplementary diets to a child’s food after the first six months of life, so mothers’ information about the nutritional needs of children is an important part of their children’s lives, and the correct weaning practices are necessary to prevent complications. Therefore, this descriptive study aimed to assess mothers’ information about infant weaning practices. This research was conducted in primary health care centers in the city of Lattakia on a sample of 100 mothers who were selected using an convenient sample method. The data were collected using a questionnaire developed by the researcher. the results of the study showed that the total level of mothers’ information about weaning was average for the highest percentage of them 62%, good level for 33% and poor level for only 5%. The study recommended identifying effective strategies for health education, including: awareness campaigns at all levels, preparing booklets that include comprehensive information on weaning to be distributed to mothers who visit the pediatric clinic with infants, and conducting training courses for nursing staff to enhance their role in educating mothers about weaning..